Isokinetic eccentric resistance training prevents loss in mechanical muscle function after running - Oliveira, Anderson Souza [UNESP]; Caputo, Fabrizio [UNESP]; Aagaard, Per; Corvino, Rogério Bulhões [UNESP]; Gonçalves, Mauro [UNESP]; Denadai, Benedito Sergio [UNESP] (Springer Nature, 2013)
The aim of the study was to verify whether 8 weeks of resistance training employing maximal isokinetic eccentric (IERT) knee extensor actions would reduce the acute force loss observed after high-intensity treadmill running exercise. It was hypothesized that specific IERT would induce protective effects against muscle fatigue and ultrastructural damages, preventing or reducing the loss in mechanical muscle function after running. Subjects were tested before and after IERT protocol for maximal isometric, concentric and eccentric isokinetic knee extensor strength (60 and 180 s-1). In a second session, subjects performed treadmill running (~35 min) and the previously mentioned measurements were repeated immediately after running. Subsequently, subjects were randomized to training (n = 12) consisting of 24 sessions of maximal IERT knee extensors actions at 180 s-1, or served as controls (n = 8). The effects of acute running-induced fatigue and training on isokinetic and isometric peak torque, and rate of force development (RFD) were investigated. Before IERT, running-induced eccentric torque loss at 180 s-1 was -8 %, and RFD loss was -11 %. Longitudinal IERT led to reduced or absent acute running-induced losses in maximal IERT torque at 180 s-1 (+2 %), being significantly reduced compared to before IERT (p < 0.05), however, RFD loss remained at -11 % (p > 0.05). In conclusion, IERT yields a reduced strength loss after high-intensity running workouts, which may suggest a protective effect against fatigue and/or morphological damages. However, IERT may not avoid reductions in explosive muscle actions. In turn, this may allow more intense training sessions to be performed, facilitating the adaptive response to running training. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Eccentric; Isokinetics; Isometric; Resistance training; Running; Stretch-shortening cycle